Disjunct populations of European vascular plant species keep the same climatic niches. Issue 12 (15th September 2015) - Wasof, Safaa; Lenoir, Jonathan; Aarrestad, Per Arild; Alsos, Inger Greve; Armbruster, W. Scott; Austrheim, Gunnar; Bakkestuen, Vegar; Birks, H. John B.; Bråthen, Kari Anne; Broennimann, Olivier; Brunet, Jörg; Bruun, Hans Henrik; et al.
Abstract: Aim: Previous research on how climatic niches vary across species ranges has focused on a limited number of species, mostly invasive, and has not, to date, been very conclusive. Here we assess the degree of niche conservatism between distant populations of native alpine plant species that have been separated for thousands of years. Location: European Alps and Fennoscandia. Methods: Of the studied pool of 888 terrestrial vascular plant species occurring in both the Alps and Fennoscandia, we used two complementary approaches to test and quantify climatic‐niche shifts for 31 species having strictly disjunct populations and 358 species having either a contiguous or a patchy distribution with distant populations. First, we used species distribution modelling to test for a region effect on each species' climatic niche. Second, we quantified niche overlap and shifts in niche width (i.e. ecological amplitude) and position (i.e. ecological optimum) within a bi‐dimensional climatic space. Results: Only one species (3%) of the 31 species with strictly disjunct populations and 58 species (16%) of the 358 species with distant populations showed a region effect on their climatic niche. Niche overlap was higher for species with strictly disjunct populations than for species with distant populations and highest for arctic–alpine species. Climatic niches were, on average, wider and located towards warmer and wetter conditions in the Alps. Main conclusion: Climatic niches seem to be generally conserved between populations that are separated between the Alps and Fennoscandia and have probably been so for 10, 000–15, 000 years. Therefore, the basic assumption of species distribution models that a species' climatic niche is constant in space and time – at least on time scales 10 4 years or less – seems to be largely valid for arctic–alpine plants.